Broiler performance and digestibility of sorghum or millet diets with enzymatic complexes - Leite, Paulo Ricardo Sá da Costa; Leandro, Nadja Susana Mogyca; Stringhini, José Henrique; Café, Marcos Barcellos; Gomes, Natali Almeida; Jardim Filho, Roberto de Moraes (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the digestibility of sorghum (Sorghum bicolor) or millet (Pennisetum glaucum) diets with the addition of a commercial enzymatic complex formed by amylase, carbohydrases, proteases and phytase, and broiler performance. For performance evaluation, 1,800 male broilers were distributed in a randomized complete block design in a 2x2 factorial arrangement, with four treatments (sorghum or millet diet with or without addition of enzymatic complex), and five replicates of 60 birds per experimental unit. In the metabolism assays carried out at 10 to 14 and 24 to 28 days, 420 male broilers were distributed in a completely randomized block design in a 2x2 factorial arrangement (millet or sorghum diet with or without addition of enzymatic complex). Data were submitted to variance analysis and averages were compared by the F test for orthogonal contrasts. In diets formulated with sorghum, the addition of the enzymatic complex provided better coefficients of digestibility of fat and nitrogen. The addition of the enzymatic complex in diets formulated with sorghum improves feed conversion ratio only in the initial phase of raising broilers, while the addition of the enzymatic complex does not improve broiler performance in diets formulated with pearl millet.